Abstract Number ‐ 188: Rescue Stenting for Intracranial Stenosis In ELVO patients Using Neuroform Atlas Stent Through Gateway Balloon - Muhammad Z Memon; Arundhati Biswas; Mohamad Ezzeldin; Taha Nisar; Amit Singla; Osama O Zaidat; Priyank Khandelwal (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Management of acute large vessel occlusion due to intracranial stenosis remains challenging with high complication and poor recanalization rates. Morbidity is also related to the intracranial exchange that is required for stent placement after the rescue angioplasty. We aim to present our initial experience of deployment of Neuroform Atlas stent through the lumen of a Gateway angioplasty balloon to avoid microcatheter exchange. Methods Patients were identified from prospectively collected mechanical thrombectomy stroke database from Feb 2019 to July 2021. Demographic and clinical information was collected. Primary outcomes were favorable functional outcome at hospital discharge (modified Rankin Scale (mRS) score of 0–3), and the rate of intracranial hemorrhage (ICH). Good angiographic recanalization (TICI ≥ 2b), and mortality at 30 days were other outcomes. Results We identified 5 patients treated with this approach [mean age 54 ± 14 years, all were men] who presented with large vessel occlusion of middle cerebral artery. Initial median NIHSS was 8 (range 6–16) with one patient received IV t‐PA. Patient initially underwent mechanical thrombectomy using the Solumbra technique. Due to reocclusion or impending occlusion with evidence of atherosclerotic plaque, rescue angioplasty with stent placement was performed. Patients were loaded with 650 mg of aspirin and 180 mg of ticagrelor through nasogastric tube prior. Balloon angioplasty was performed using the gateway balloon size ranging from 1.5 to 3 mm which was inflated to subnominal pressures over 1 minutes. This was followed by placing Neuroform atlas stent through the gateway balloon with size ranging from 3 to 4 mm diameter and length ranges from 21–24 mm. TICI ≥ 2b was achieved in 4 patients. Mean time from symptoms onset to revascularization was (336 ± 90) minutes. One patient had asymptomatic ICH. 2 patients had mRs 0–3 at the time of discharge and one patient was dead at 1 month Conclusions Our preliminary experience showed lower risk of guidewire perforation as well as potentially decreased operative time and early reperfusion by deploying the Neuroform stent through a compatible gateway balloon microcatheter. This should be investigated further in a large multicenter study